Surfacing effects on thermal condition in urban open space / Liyana Ahmad Bazuli and Azhan Abdul Aziz - Ahmad Bazuli, Liyana; Abdul Aziz, Azhan (2015)
Urban density has significant impacts in shaping the microclimatic condition of urban milieu. Studies related to global warming and environmental hazard effecting climate condition particularly in urban open space indicates constructive outcomes of escalating temperature caused by poor design strategies and adaptation. Hence, the aim of this study is to identify and assess the elements and prospects of existing open space towards outdoor thermal condition and discomfort of urban environments while preserving the ideal state of quality of life. Measures involve physical microclimatic parameters (radiant temperature, air velocity and relative humidity) and calculations of natural and man made topographies in two identical open spaces. Meteorological assessments was conducted at designated zones for three (3) days in June at 1.1meter above ground level with five (5) and ten (10) minutes time interval. The preliminary findings revealed that the morphological characteristics and total area of natural and man made elements affect the thermal condition of urban open spaces. However, further empirical research is required to include other associated parameters i.e. types of vegetation and materials promoting ideal thermal environments.